2021
DOI: 10.3389/fpubh.2021.705597
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Needs a National Human Health Observing System

Abstract: The COVID-19 pandemic and increasing frequency and severity of environmental disasters reveal an urgent need for a robust health observing/surveillance system. With the possible exception of Brazil, we know of no such comprehensive health observing capacity. The US should create a national system of linked regionally-based health monitoring systems similar to those for weather, ocean conditions, and climate. Like those for weather, the health observing system should operate continuously, collecting mental, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…The health observing system would also include a plan for incorporation of other metrics as they become available or are identified as having particular salience. A pilot human health observing system project, perhaps located in the central Gulf of Mexico region, could be used to demonstrate the usefulness of the approach and fine-tune its design for broader implementation ( Sandifer et al 2021 ). The ultimate goal will be to build a linked network of regional health observing systems across the US (Sandifer 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The health observing system would also include a plan for incorporation of other metrics as they become available or are identified as having particular salience. A pilot human health observing system project, perhaps located in the central Gulf of Mexico region, could be used to demonstrate the usefulness of the approach and fine-tune its design for broader implementation ( Sandifer et al 2021 ). The ultimate goal will be to build a linked network of regional health observing systems across the US (Sandifer 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed several criticisms of the lack of availability of baseline health data captured before, during, and on an ongoing basis after a disaster, pointing out that health monitoring is essential to reduce and manage the health impacts of future disasters and that it is also necessary to establish an observation and care system 73 . The Unified Health System (SUS) is internationally recognized for its ability to realize extensive monitoring of human health regarding disasters and may be an example to be followed by other countries 73, 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas recentes revelaram várias críticas à falta de disponibilidade de dados de saúde de linha de base capturados antes, durante e de forma contínua após um desastre, apontando que o monitoramento da saúde é essencial para reduzir e gerenciar impactos na saúde de desastres futuros, sendo necessário ainda o estabelecimento de um sistema de observação e cuidado 73 . O Sistema Único de Saúde (SUS) é reconhecido internacionalmente pela sua capacidade em realizar um grande monitoramento de saúde humana em relação a desastres, podendo ser um exemplo a ser seguido por outros países 73, 74 .…”
Section: Entre As Ações E As Críticas: Caminhos Tomados Pelos Governosunclassified